Nocturnal Gastroesophageal Reflux Revisited by Impedance-pH Monitoring - Fornari, Fernando (Korean Society of Neurogastroenterology and Motility, 2011)
BACKGROUND/AIMS: Impedance-pH monitoring allows detailed characterization of gastroesophageal reflux and esophageal activity associated with reflux. We assessed the characteristics of nocturnal reflux and esophageal activity preceding and following reflux. METHODS: Impedance-pH tracings from 11 healthy subjects and 76 patients with gastroesophageal reflux disease off acid-suppressive therapy were analyzed. Characteristics of nocturnal supine reflux, time distribution and esophageal activity seen on impedance at 2 minute intervals preceding and following reflux were described. RESULTS: Patients had more nocturnal reflux events than healthy subjects (8 [4-12] vs 2 [1-5], P = 0.002), with lower proportion of weakly acidic reflux (57% [35-78] vs 80% [60-100], P = 0.044). Nocturnal reflux was mainly liquid (80%) and reached the proximal esophagus more often in patients (6% vs 0%, P = 0.047). Acid reflux predominated in the first 2 hours (66%) and weakly acidic reflux in the last 3 hours (70%) of the night. Most nocturnal reflux was preceded by aboral flows and cleared by short lasting volume clearance. In patients, prolonged chemical clearance was associated with less esophageal activity. CONCLUSIONS: Nocturnal weakly acidic reflux is as common as acid reflux in patients with gastroesophageal reflux disease, and predominates later in the night. Impedance-pH can predict prolonged chemical clearance after nocturnal acid reflux.